2015
DOI: 10.1371/journal.pone.0129477
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Durability of Initial Combination Therapy with Sitagliptin and Metformin in Patients with Type 2 Diabetes in Clinical Practice; COSMIC Study

Abstract: ObjectivesWe investigated the efficacy of initial combination therapy with sitagliptin and metformin in patients with type 2 diabetes for 4 years in clinical practice.MethodsBetween 2009 and 2010, we reviewed 1,178 patients with type 2 diabetes (HbA1c ≥7.5% or 58 mmol/mol) prescribed initial combination therapy with sitagliptin and metformin. After excluding 288 patients without a second follow-up, 890 individuals (age, 58.0 ± 12.5 years; BMI, 25.4 ± 3.5 kg/m2; HbA1c, 8.6 ± 1.1%) were followed up with every 3–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
12
1
2
Order By: Relevance
“…C-peptide immunoreactivity was not associated with a reduction in FPG and HbA1c in both the metformin and alogliptin groups in the present study. This finding is in contrast to that of a recent clinical trial in which low baseline b-cell function was an independent predictor of a good response in participants undergoing combination therapy with sitagliptin and metformin 32 . The administration of x-3 polyunsaturated fatty acids has been reported to induce GLP-1 secretion in mice 33,34 .…”
Section: Discussioncontrasting
confidence: 99%
“…C-peptide immunoreactivity was not associated with a reduction in FPG and HbA1c in both the metformin and alogliptin groups in the present study. This finding is in contrast to that of a recent clinical trial in which low baseline b-cell function was an independent predictor of a good response in participants undergoing combination therapy with sitagliptin and metformin 32 . The administration of x-3 polyunsaturated fatty acids has been reported to induce GLP-1 secretion in mice 33,34 .…”
Section: Discussioncontrasting
confidence: 99%
“…Not surprisingly, results from several studies have shown that initial combination therapy with metformin and a DPP-4 inhibitor provides greater improvement in glycemic control than monotherapy with either agent [14,[18][19][20]. For example, results from a 24-week study with linagliptin plus metformin demonstrated greater placebo-corrected reductions in HbA1c with initial combination therapy than monotherapy with either component: -1.7% for linagliptin 5 mg/metformin 2000 mg, -1.3% for linagliptin 5 mg/metformin 1000 mg, -1.2% for metformin 2000 mg, -0.8% for metformin 1000 mg, and -0.6% for linagliptin 5 mg (all p \ 0.0001) [18].…”
Section: Efficacy Considerations With a Combination Of Metformin And mentioning
confidence: 99%
“…An XE-2100 Hematology Analyzer is used for measuring the white blood cell count, hemoglobin level, hematocrit, and platelet count. Aspartate and alanine aminotransferase (NADH-UV method), total bilirubin (bilirubin oxidase method), thyroid function test (electrochemiluminescence immunoassay), blood urea nitrogen (urease/GLDH method), creatinine (Jaffe's kinetic method), calcium (OC/PC method), and phosphorus (Molybdate reduction method) are measured at the central laboratory of SNUBH, as reported previously 32,33) . The biochemical tests are done immediately after sample collection.…”
Section: ) Baseline Studymentioning
confidence: 99%